2016
DOI: 10.1017/s0033291716001963
|View full text |Cite
|
Sign up to set email alerts
|

Neural alterations of fronto-striatal circuitry during reward anticipation in euthymic bipolar disorder

Abstract: BackgroundBipolar disorder (BD), with the hallmark symptoms of elevated and depressed mood, is thought to be characterized by underlying alterations in reward-processing networks. However, to date the neural circuitry underlying abnormal responses during reward processing in BD remains largely unexplored. The aim of this study was to investigate whether euthymic BD is characterized by aberrant ventral striatal (VS) activation patterns and altered connectivity with the prefrontal cortex in response to monetary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 46 publications
3
34
1
Order By: Relevance
“…More than 50% of patients with chronic pain suffer from depression (Chopra and Arora, ). Abnormality of the NAc is associated with depression (McCabe, ) and mood disorders (Schreiter et al., ). Pain catastrophizing is a negative cognitive and emotional response to pain involving factors of rumination, magnification and feeling of helplessness (Quartana et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…More than 50% of patients with chronic pain suffer from depression (Chopra and Arora, ). Abnormality of the NAc is associated with depression (McCabe, ) and mood disorders (Schreiter et al., ). Pain catastrophizing is a negative cognitive and emotional response to pain involving factors of rumination, magnification and feeling of helplessness (Quartana et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently euthymic individuals with a BSD exhibit higher self-reported reward sensitivity and increased behavioral and neurophysiological responses to rewards on reward-related tasks (see Alloy et al, 2016;Nusslock & Alloy, 2017, for reviews). In addition, fMRI studies employing reward task paradigms provide support for elevated VS and OFC reward responses in both manic and euthymic individuals with bipolar I and II disorders, and individuals at risk for BSD (see Alloy et al, 2016;Nusslock & Alloy, 2017, for reviews; but see Schreiter et al, 2016, andYip, Worhunsky, Rogers, &Goodwin, 2015, for alternative findings). Using diffusion imaging, Damme et al (2017) found that individuals at risk for BSD also show enhanced corticostriatal structural connectivity compared to low-risk individuals.…”
Section: Evidence For the Reward Hypersensitivity Model In Bsdsmentioning
confidence: 99%
“…In addition, several functional MRI studies examined functional connectivity of the ventral striatum in a reward context. For example, Schreiter and colleagues (2016) showed decreased functional connectivity between the left ventral striatum and anterior prefrontal cortex in patients with bipolar disorder during reward anticipation. Weiland et al (2013) demonstrated increased connectivity between the ventral striatum and both paracentral lobule/precuneus and sensorimotor areas in youth with a family history of alcoholism during incentive anticipation (both reward and loss conditions).…”
Section: Discussionmentioning
confidence: 99%